'Cry "HAVOC!" and Let Slip the Dogs of War': Regulating Private Military and Security Companies. Issue 1 (June 2016) - Van Oeveren, Anna
The second biggest contingent in Iraq after US forces, contractors have become something of a staple in contemporary conflict resolution and peacekeeping operations. The rise of private security and military firms is not a recent phenomenon. It has been a given since the end of the Cold War, thanks to a particular momentum in the market for force. Traditional armed forces have had their budgets cut and have sometimes had to undergo drastic economic reforms. At the same time, the market for force has seen the arrival of huge numbers of highly qualified military personnel. These developments have been beneficial to the rise of private military and security companies. However, they have also exposed the weakness of international law and regulation (and EU regulation in particular) when it comes to dealing with these firms.